(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
In this article, the author examines important aspects of US strategic interests in Central Asia, primarily related to the aspirations of the United States and its NATO partners to achieve their political and military goals in Afghanistan and the Central Asian region. Also, the peculiarities of the implementation of the plans of Western countries led by the United States with the deployment of military bases on the territory of the states of the region, from which not only the penetration of foreign troops into Afghanistan was carried out, but also comprehensive support during the operation "Unbending Freedom".